Determinants of mortgage arrears in Europe: evidence from household microdata. Issue 4 (2nd October 2018) - Gerlach-Kristen, Petra; Lyons, Seán
Abstract : In purely economic terms, mortgage arrears can pose a risk to the stability of banks and limit households' future access to credit. Moreover, arrears have social ramifications: they reduce aspects of households' well-being and health, and addressing such negative effects can lead to a requirement for higher social spending by governments. It is therefore important to identify the drivers of arrears and design policies to reduce them. We use a European household data-set to analyse what drives arrears. Controlling for household characteristics such as age and education, we find that affordability problems, such as unemployment, low income and high mortgage payments, matter. Households facing the dual trigger of affordability problems and negative equity are more likely to go into longer- term arrears. We also find that households in Cyprus and Greece are particularly prone to miss mortgage payments, while those in the United Kingdom and Belgium are very unlikely to do so. Generally, arrears tend to be higher in poor countries and where investors' rights are poorly protected.